Study on “three places and four fields” airline resource cooperative allocation based on decision tree algorithm - Luo, Dingfa (E3S web of conferences, 2024)
In view of the disharmony development status of Beijing Tianjin Hebei region, the paper puts forward a route optimization Principle of cooperative allocation of route resources of airport group from the angle of flight punctuality, airlines share and function orientation. An optimal model of airline resources cooperative allocation is established to maximize the overall operational benefit of regional airports and the modified decision tree C4.5 algorithm was applied to solve the problem. Since this algorithm combined with constraint condition of model as pruning standard, the efficiency of the algorithm was greatly improved. Finally, the problem find the optimal solution could be found by comparing the profit and loss value of the program. The analysis example showed that the overall benefit of multi-airport system increased by 7.03%. This model was useful to optimize airline network and conformed to the actual situation, and the research results can provide a reference for civil aviation authorities in planning the airline network of multi-airport system.